A hydrophobic, lipophilic, and skin-friendly ultrafine powder and its preparation method and application

Through sol-gel reaction and multi-layer surface modification technology, titanium dioxide/zinc oxide nanoparticle composite materials with high whiteness and good weather resistance were prepared, solving the problems of poor hydrophilicity and photochemical activity of existing TiO2 in cosmetics, and achieving efficient sun protection and whitening and improving skin feeling.

CN118845501BActive Publication Date: 2025-04-15广州晋航生物科技有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410875373.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-02
Publication Date
2025-04-15
Estimated Expiration
2044-07-02

AI Technical Summary

Technical Problem

The existing TiO2 application in cosmetics has problems such as poor hydrophilicity, easy agglomeration, poor dispersion, and photochemical activity leading to coating powdering, loss of light, and reduced weather resistance, and high content of titanium dioxide increases costs.

Method used

Titanium dioxide/zinc oxide nanoparticles were prepared by sol-gel reaction, and polydopamine modification was carried out, calcium hydroxide reacted with sodium oleate and sodium stearate to form calcium carbonate and calcium stearate precipitate. Combined with composite silane and macadamia seed oil polyglycerol-6 ester beanate bentoate, hydrophobic oleophilic and skin-friendly ultrafine powder was prepared.

Benefits of technology

It has achieved the preparation of titanium dioxide composite materials with high whiteness, low cost, good weather resistance, good dispersion and strong ultraviolet absorption capacity. It has good concealment effect, sun protection and whitening effect, improved skin feeling, smooth and delicate, good ductility, long makeup time, moisturizing and oil control effects, and reduce collective aggregation during the dispersion process to avoid dust.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention proposes a hydrophobic, lipophilic, skin-friendly ultrafine powder and a preparation method and application thereof, belonging to the technical field of cosmetics. It includes: S1. Preparation of titanium dioxide / zinc oxide nanoparticles; S2. Polydopamine modification; S3. Surface modification; S4. Silane modification; S5. Preparation of hydrophobic, lipophilic, skin-friendly ultrafine powder. The hydrophobic, lipophilic, skin-friendly ultrafine powder prepared by the present invention has a good concealing effect, a certain sunscreen and whitening effect, can improve skin feel, is smooth and delicate, has good ductility, has a long makeup-lasting time, has a certain moisturizing effect and oil control effect, has good dispersibility, good stability, reduces collective aggregation during the dispersion process, and effectively avoids dust.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cosmetics, and in particular to a hydrophobic, lipophilic and skin-friendly ultrafine powder and a preparation method and application thereof. Background Art

[0002] TiO2 is an important white inorganic pigment. It is widely used in sunscreen skin care products, pressed powder, foundation cream, liquid foundation, lip beauty products, eye beauty products, nail beauty products and other cosmetics due to its excellent reflection and scattering of ultraviolet rays, chemical stability and thermal stability, high whiteness and gloss, good dispersibility and weather resistance, high tinting power and hiding power, and safety and non-toxicity. However, untreated TiO2 ultrafine particles have a large specific surface area and high surface energy, showing strong hydrophilicity and oleophobicity, which makes it easy to agglomerate in organic systems, poor compatibility and dispersibility. At the same time, the photochemical activity of TiO2 will cause complex chemical reactions in the surrounding organic medium under light irradiation, resulting in powdering, loss of gloss and reduced weather resistance of the coating film, so its surface must be organically coated.

[0003] Organic coating on the surface of TiO2 has become the most important core competitive ability of TiO2 in the high-end cosmetics industry. The methods of organic coating on the surface of TiO2 can be divided into esterification method, surfactant method, coupling agent method and polymer coating method according to the type of coated organic matter. Among them, the coupling agent method has attracted widespread attention because it can form strong chemical bonds through the groups at both ends of the coupling agent with TiO2 inorganic powder and organic polymer, and firmly combine TiO2 and organic matrix, two materials with very different properties. At present, the most commonly used coupling agent is silane coupling agent, which can give the cosmetic coating added with TiO2 particles a hydrophobic effect, but it is lipophilic and can absorb the oil secreted by the skin and destroy the makeup. Moreover, the coupling agent can only form a single layer coating on the surface of TiO2 and cannot completely cover the photochemical active points on the surface of TiO2 particles; the polymer coating method can form a film layer of a certain thickness on the surface of TiO2 particles, but most of them are distributed on the surface of TiO2 particles in a physical winding manner, and are easy to fall off due to weak binding force. And the high content of titanium dioxide makes its cost higher.

[0004] Therefore, how to effectively overcome the defects in the above-mentioned prior art and obtain a titanium dioxide composite material with high whiteness, low cost, good weather resistance, good dispersibility and strong ultraviolet absorption ability is of great significance for improving the application value and application scope of titanium dioxide in cosmetics. Summary of the invention

[0005] The purpose of the present invention is to propose a hydrophobic, lipophilic, skin-friendly ultrafine powder and a preparation method and application thereof, which has good blemish-covering effect, certain sunscreen and whitening effect, can improve skin feel, is smooth and delicate, has good ductility, has a long makeup-lasting time, has certain moisturizing effect and oil-control effect, has good dispersibility and stability, reduces collective aggregation during the dispersion process, and effectively avoids dust.

[0006] The technical solution of the present invention is achieved in this way:

[0007] The present invention provides a method for preparing a hydrophobic, lipophilic and skin-friendly ultrafine powder, comprising the following steps:

[0008] S1. Preparation of titanium dioxide / zinc oxide nanoparticles: tetrabutyl titanate and zinc acetate are dissolved in ethanol, polyethylene glycol 400, ammonia water and water are added, stirred for reaction, centrifuged, washed, dried, and calcined to obtain titanium dioxide / zinc oxide nanoparticles;

[0009] S2. Polydopamine modification: The titanium dioxide / zinc oxide nanoparticles prepared in step S1 are added to water, dopamine hydrochloride and a catalyst are added, the reaction is heated and stirred, centrifuged, washed, and dried to obtain polydopamine titanium dioxide / zinc oxide nanoparticles;

[0010] S3 surface modification: the polydopamine-modified titanium dioxide / zinc oxide nanoparticles prepared in step S2 were added to a calcium hydroxide solution, sodium oleate and sodium stearate were added dropwise, a mixed gas was introduced, the reaction was stirred, and modified nanoparticles were obtained;

[0011] S4. Silane modification: adding the modified nanoparticles obtained in step S3 to ethanol, adding the composite silane, stirring the reaction, centrifuging, washing, and drying to obtain silane-modified nanoparticles;

[0012] S5. Preparation of hydrophobic, lipophilic, and skin-friendly ultrafine powder: Add the silane-modified nanoparticles obtained in step S4 to ethanol, add macadamia seed oil polyglycerol-6 ester behenate, stir to react, centrifuge, wash, and dry to obtain a hydrophobic, lipophilic, and skin-friendly ultrafine powder.

[0013] As a further improvement of the present invention, the mass ratio of tetrabutyl titanate, zinc acetate, polyethylene glycol 400, ammonia water and water in step S1 is 9-11:3-5:0.5-1:4-6:7-10, the stirring reaction time is 30-50 minutes, the calcination temperature is 350-450°C, and the time is 1-3 hours.

[0014] As a further improvement of the present invention, the mass ratio of the titanium dioxide / zinc oxide nanoparticles, dopamine hydrochloride and the catalyst in step S2 is 10:3-4:0.1-0.2, the catalyst is a Tris-HCl solution with a pH of 8.5-9, the temperature of the heating and stirring reaction is 40-50°C, and the time is 1-2h.

[0015] As a further improvement of the present invention, the mass ratio of the polydopamine-modified titanium dioxide / zinc oxide nanoparticles, sodium oleate and sodium stearate in step S3 is 10:1-2:2-3, the concentration of calcium hydroxide in the calcium hydroxide solution is 0.1-0.15wt%, the mixed gas is a mixed gas of CO2 and N2, the volume ratio is 3-4:10, the ventilation volume is 3-5mL / s, and the stirring reaction time is 30-50min.

[0016] As a further improvement of the present invention, the mass ratio of the modified nanoparticles and the composite silane in step S4 is 100:7-10, the composite silane is phenyl polytrimethylsiloxane and KH580, the mass ratio is 10:3-5, the stirring reaction temperature is 35-45°C, and the time is 1-3h; the mass ratio of the silane-modified nanoparticles and macadamia seed oil polyglycerol-6 ester behenate in step S5 is 50:7-10, and the stirring reaction time is 20-40min.

[0017] As a further improvement of the present invention, the present invention specifically comprises the following steps:

[0018] S1. Preparation of titanium dioxide / zinc oxide nanoparticles: 9-11 parts by weight of tetrabutyl titanate and 3-5 parts by weight of zinc acetate are dissolved in ethanol, 0.5-1 parts by weight of polyethylene glycol 400, 4-6 parts by weight of ammonia water and 7-10 parts by weight of water are added, the reaction is stirred for 30-50 minutes, centrifuged, washed, dried, and calcined at 350-450° C. for 1-3 hours to obtain titanium dioxide / zinc oxide nanoparticles;

[0019] S2. Polydopamine modification: 10 parts by weight of the titanium dioxide / zinc oxide nanoparticles prepared in step S1 were added to water, 3-4 parts by weight of dopamine hydrochloride and 0.1-0.2 parts by weight of a catalyst were added, heated to 40-50 ° C, stirred for 1-2h, centrifuged, washed, and dried to obtain polydopamine titanium dioxide / zinc oxide nanoparticles;

[0020] The catalyst is a Tris-HCl solution with a pH of 8.5-9;

[0021] S3. Surface modification: 10 parts by weight of the polydopamine-modified titanium dioxide / zinc oxide nanoparticles prepared in step S2 were added to a 0.1-0.15wt% calcium hydroxide solution, 1-2 parts by weight of sodium oleate and 2-3 parts by weight of sodium stearate were added dropwise, and the mixed gas was introduced at a flow rate of 3-5mL / s, and the reaction was stirred for 30-50min to obtain modified nanoparticles;

[0022] The mixed gas is a mixed gas of CO2 and N2, with a volume ratio of 3-4:10;

[0023] S4 silane modification: 100 parts by weight of the modified nanoparticles obtained in step S3 were added to ethanol, 7-10 parts by weight of the composite silane was added, the reaction was stirred at 35-45 ° C for 1-3h, centrifuged, washed, and dried to obtain silane-modified nanoparticles;

[0024] The composite silane is phenyl polytrimethylsiloxane and KH580, with a mass ratio of 10:3-5;

[0025] S5. Preparation of hydrophobic, lipophilic, and skin-friendly ultrafine powder: add 50 parts by weight of the silane-modified nanoparticles obtained in step S4 to ethanol, add 7-10 parts by weight of macadamia seed oil polyglycerol-6 ester behenate, stir to react for 20-40 minutes, centrifuge, wash, and dry to obtain a hydrophobic, lipophilic, and skin-friendly ultrafine powder.

[0026] The present invention further protects a hydrophobic, lipophilic and skin-friendly ultrafine powder obtained by the above-mentioned preparation method.

[0027] The present invention further protects the use of the above-mentioned hydrophobic, lipophilic and skin-friendly ultrafine powder in the preparation of cosmetics.

[0028] The present invention further protects a water-sense long-lasting makeup cushion, comprising: component A1, component A2, component A3, component B and component C, with a mass ratio of 20-25:18-20:4-5:40-45:0.04-0.07, wherein component A1 is prepared from the following raw materials by weight: 8-10 parts of the above-mentioned hydrophobic, lipophilic and skin-friendly ultrafine powder, 2-4 parts of caprylic / capric triglyceride; component A2 is prepared from the following raw materials by weight: 10-12 parts of cyclopentasiloxane, 1-1.5 parts of trimethylsiloxysilicate; component A3 is prepared from the following raw materials by weight: 0.05-0.1 parts of disteardimethylammonium hectorite, 1-1.5 parts of polydimethylsiloxane / vinyl polydimethylsiloxane crosslinked polymer, PEG-10 2-2.5 parts; component B is prepared from the following raw materials by weight: 35-40 parts of water, 0.01-0.02 parts of disodium EDTA, 0.3-0.4 parts of magnesium sulfate, 3-4 parts of butylene glycol, 2-3 parts of glycerol, 1-2 parts of 1,2-pentanediol, 0.2-0.4 parts of ethylhexylglycerol, and 0.01-0.1 parts of phenoxyethanol; component C is essence.

[0029] The present invention further protects a method for preparing the above-mentioned water-sense long-lasting makeup cushion, comprising the following steps:

[0030] (1) Grind the raw materials of component A1 evenly and set aside;

[0031] (2) Heat component A2 to 80-85°C, stir and mix evenly, and set aside;

[0032] (3) Add components A1 and A3 to component A2, raise the temperature to 70-75°C, and stir to disperse evenly;

[0033] (4) Component B is heated to 70-75° C., added to the system in step (3), homogenized until fully emulsified, cooled to 40-45° C., component C is added, stirred evenly, filtered, and filled to obtain a water-based long-lasting makeup cushion.

[0034] The present invention has the following beneficial effects:

[0035] The present invention adopts sol-gel reaction to prepare titanium dioxide / zinc oxide nanoparticles, which have small particle size and uniform size. At the same time, titanium dioxide and zinc oxide have good whiteness, good blemish-covering effect, and can reflect and scatter ultraviolet light, so that ultraviolet light cannot directly reach the skin, thus achieving good sunscreen effect. At the same time, they have good photocatalytic antibacterial effect, have good antibacterial, mite-removing and anti-inflammatory effects on the skin, and are safe and have no side effects.

[0036] However, the titanium dioxide / zinc oxide nanoparticles have good hydrophilicity but poor lipophilicity, are easy to agglomerate, and have poor dispersibility, which greatly limits their application in cosmetics. The present invention modifies the surface of the titanium dioxide / zinc oxide nanoparticles prepared by polydopamine, so that the nanoparticles are easy to adsorb calcium hydroxide, and after the mixed gas is introduced, calcium carbonate precipitates are formed on the surface of the polydopamine titanium dioxide / zinc oxide nanoparticles. At the same time, under the action of sodium oleate and sodium stearate, calcium hydroxide reacts with the nanoparticles to form calcium oleate and calcium stearate, which are deposited on the surface of calcium carbonate, greatly reducing its surface energy, so that the hydrophobicity of the prepared modified nanoparticles is improved, and the nanoparticles have good lipophilicity.

[0037] The present invention further reacts the prepared modified nanoparticles with composite silane, so that the prepared hydrophobic, lipophilic, and skin-friendly ultrafine powder is more skin-friendly and gentle. At the same time, the thiol group can fit well with the skin, prolonging the makeup-holding time, and making the skin feel more close to the makeup, not greasy and occlusive, and more comfortable to wear.

[0038] The prepared silane-modified nanoparticles are mixed and modified with macadamia nut oil polyglycerol-6 ester behenate, which has a melting point of about 37° C. When applied on the skin, it feels melted and has good smoothness and skin-fitting properties, making the product more skin-friendly.

[0039] The hydrophobic, lipophilic, and skin-friendly ultrafine powder prepared by the present invention has good blemish-covering effect, certain sunscreen and whitening effect, can improve skin feel, is smooth and delicate, has good ductility, has a long makeup-lasting time, has certain moisturizing and oil-control effects, has good dispersibility and stability, reduces collective aggregation during the dispersion process, and effectively avoids dust.

[0040] The water-sense long-lasting makeup air cushion made of the hydrophobic, lipophilic, skin-friendly ultrafine powder of the present invention has an excellent skin feel and a good makeup-lasting effect, has a certain moisturizing effect and an oil-control effect, and has sun protection and whitening effects, and is popular among consumers. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] This embodiment provides a method for preparing a hydrophobic, lipophilic, and skin-friendly ultrafine powder, which specifically comprises the following steps:

[0044] S1. Preparation of titanium dioxide / zinc oxide nanoparticles: 9 g of tetrabutyl titanate and 3 g of zinc acetate were dissolved in 100 mL of ethanol, 0.5 g of polyethylene glycol 400, 4 g of ammonia water and 7 mL of water were added, the mixture was stirred for 30 min, centrifuged, washed, dried, and calcined at 350 ° C for 1 h to obtain titanium dioxide / zinc oxide nanoparticles;

[0045] S2. Polydopamine modification: 10 g of the titanium dioxide / zinc oxide nanoparticles prepared in step S1 was added to 100 mL of water, 3 g of dopamine hydrochloride and 0.1 g of a catalyst were added, heated to 40 ° C, stirred for 1 h, centrifuged, washed, and dried to obtain polydopamine titanium dioxide / zinc oxide nanoparticles;

[0046] The catalyst is a Tris-HCl solution with a pH of 8.5;

[0047] S3. Surface modification: 10 g of the polydopamine-modified titanium dioxide / zinc oxide nanoparticles prepared in step S2 were added to 100 mL of a 0.1 wt% calcium hydroxide solution, 1 g of sodium oleate and 2 g of sodium stearate were added dropwise, the mixed gas was introduced at a flow rate of 3 mL / s, and the reaction was stirred for 30 min to obtain modified nanoparticles;

[0048] The mixed gas is a mixed gas of CO2 and N2, with a volume ratio of 3:10;

[0049] S4 silane modification: 100 parts by weight of the modified nanoparticles obtained in step S3 were added to ethanol, 7 parts by weight of the composite silane were added, the reaction was stirred at 35 ° C for 1h, centrifuged, washed, and dried to obtain silane-modified nanoparticles;

[0050] The composite silane is phenyl polytrimethylsiloxane and KH580, with a mass ratio of 10:3;

[0051] S5. Preparation of hydrophobic, lipophilic, and skin-friendly ultrafine powder: Add 50 parts by weight of the silane-modified nanoparticles obtained in step S4 to ethanol, add 7 parts by weight of macadamia seed oil polyglycerol-6 ester behenate, stir and react for 20 minutes, centrifuge, wash, and dry to obtain a hydrophobic, lipophilic, and skin-friendly ultrafine powder.

[0052] Example 2

[0053] This embodiment provides a method for preparing a hydrophobic, lipophilic, and skin-friendly ultrafine powder, which specifically comprises the following steps:

[0054] S1. Preparation of titanium dioxide / zinc oxide nanoparticles: 11 g of tetrabutyl titanate and 5 g of zinc acetate were dissolved in 100 mL of ethanol, 1 g of polyethylene glycol 400, 6 g of ammonia water and 10 mL of water were added, stirred for 50 min, centrifuged, washed, dried, and calcined at 450° C. for 3 h to obtain titanium dioxide / zinc oxide nanoparticles;

[0055] S2. Polydopamine modification: 10 g of the titanium dioxide / zinc oxide nanoparticles prepared in step S1 was added to 100 mL of water, 4 g of dopamine hydrochloride and 0.2 g of a catalyst were added, heated to 50 ° C, stirred for 2 h, centrifuged, washed, and dried to obtain polydopamine titanium dioxide / zinc oxide nanoparticles;

[0056] The catalyst is a Tris-HCl solution with a pH of 9;

[0057] S3. Surface modification: 10 g of the polydopamine-modified titanium dioxide / zinc oxide nanoparticles prepared in step S2 were added to 100 mL of a 0.15 wt% calcium hydroxide solution, 2 g of sodium oleate and 3 g of sodium stearate were added dropwise, and the mixed gas was introduced at a flow rate of 5 mL / s, and the reaction was stirred for 50 min to obtain modified nanoparticles;

[0058] The mixed gas is a mixed gas of CO2 and N2, with a volume ratio of 4:10;

[0059] S4 silane modification: 100 parts by weight of the modified nanoparticles obtained in step S3 were added to ethanol, 10 parts by weight of the composite silane was added, the reaction was stirred at 45 ° C for 3h, centrifuged, washed, and dried to obtain silane-modified nanoparticles;

[0060] The composite silane is phenyl polytrimethylsiloxane and KH580, with a mass ratio of 10:5;

[0061] S5. Preparation of hydrophobic, lipophilic, and skin-friendly ultrafine powder: Add 50 parts by weight of the silane-modified nanoparticles obtained in step S4 to ethanol, add 10 parts by weight of macadamia seed oil polyglycerol-6 ester behenate, stir and react for 40 minutes, centrifuge, wash, and dry to obtain a hydrophobic, lipophilic, and skin-friendly ultrafine powder.

[0062] Example 3

[0063] This embodiment provides a method for preparing a hydrophobic, lipophilic, and skin-friendly ultrafine powder, which specifically comprises the following steps:

[0064] S1. Preparation of titanium dioxide / zinc oxide nanoparticles: 10 g of tetrabutyl titanate and 4 g of zinc acetate were dissolved in 100 mL of ethanol, 0.7 g of polyethylene glycol 400, 5 g of ammonia water and 8 g of water were added, stirred for 40 min, centrifuged, washed, dried, and calcined at 400 ° C for 2 h to obtain titanium dioxide / zinc oxide nanoparticles;

[0065] S2. Polydopamine modification: 10 g of the titanium dioxide / zinc oxide nanoparticles prepared in step S1 was added to 100 mL of water, 3.6 g of dopamine hydrochloride and 0.12 g of the catalyst were added, heated to 45 ° C, stirred for 1.5 h, centrifuged, washed, and dried to obtain polydopamine titanium dioxide / zinc oxide nanoparticles;

[0066] The catalyst is a Tris-HCl solution with a pH of 8.7;

[0067] S3. Surface modification: 10 g of the polydopamine-modified titanium dioxide / zinc oxide nanoparticles prepared in step S2 was added to 100 mL of a 0.12 wt% calcium hydroxide solution, 1.2 g of sodium oleate and 2.7 g of sodium stearate were added dropwise, the mixed gas was introduced at a flow rate of 4 mL / s, and the reaction was stirred for 40 min to obtain modified nanoparticles;

[0068] The mixed gas is a mixed gas of CO2 and N2, with a volume ratio of 3.5:10;

[0069] S4 silane modification: 100 parts by weight of the modified nanoparticles obtained in step S3 were added to ethanol, 8.5 parts by weight of the composite silane were added, the reaction was stirred at 40 ° C for 2h, centrifuged, washed, and dried to obtain silane-modified nanoparticles;

[0070] The composite silane is phenyl polytrimethylsiloxane and KH580, with a mass ratio of 10:4;

[0071] S5. Preparation of hydrophobic, lipophilic, and skin-friendly ultrafine powder: Add 50 parts by weight of the silane-modified nanoparticles obtained in step S4 to ethanol, add 8.5 parts by weight of macadamia seed oil polyglycerol-6 ester behenate, stir and react for 30 minutes, centrifuge, wash, and dry to obtain a hydrophobic, lipophilic, and skin-friendly ultrafine powder.

[0072] Example 4

[0073] Compared with Example 3, the difference is that the composite silane is replaced by single phenyl polytrimethylsiloxane.

[0074] Example 5

[0075] Compared with Example 3, the difference is that the composite silane is replaced by a single KH580.

[0076] Comparative Example 1

[0077] Compared with Example 3, the difference is that tetrabutyl titanate is not added in step S1.

[0078] The details are as follows:

[0079] S1. Preparation of zinc oxide nanoparticles: Dissolve 16 g of zinc acetate in 100 mL of ethanol, add 1 g of polyethylene glycol 400, 6 g of ammonia water and 10 mL of water, stir and react for 50 min, centrifuge, wash, dry, and calcine at 450° C. for 3 h to obtain zinc oxide nanoparticles.

[0080] Comparative Example 2

[0081] Compared with Example 3, the difference is that zinc acetate is not added in step S1.

[0082] The details are as follows:

[0083] S1. Preparation of titanium dioxide nanoparticles: Dissolve 16 g of tetrabutyl titanate in 100 mL of ethanol, add 1 g of polyethylene glycol 400, 6 g of ammonia water and 10 mL of water, stir and react for 50 min, centrifuge, wash, dry, and calcine at 450° C. for 3 h to obtain titanium dioxide nanoparticles.

[0084] Comparative Example 3

[0085] Compared with Example 3, the difference is that step S2 is not performed.

[0086] The details are as follows:

[0087] S1. Preparation of titanium dioxide / zinc oxide nanoparticles: 10 g of tetrabutyl titanate and 4 g of zinc acetate were dissolved in 100 mL of ethanol, 0.7 g of polyethylene glycol 400, 5 g of ammonia water and 8 g of water were added, stirred for 40 min, centrifuged, washed, dried, and calcined at 400 ° C for 2 h to obtain titanium dioxide / zinc oxide nanoparticles;

[0088] S2. Surface modification: 10 g of the titanium dioxide / zinc oxide nanoparticles prepared in step S1 were added to 100 mL of a 0.12 wt% calcium hydroxide solution, 1.2 g of sodium oleate and 2.7 g of sodium stearate were added dropwise, the mixed gas was introduced at a flow rate of 4 mL / s, and the reaction was stirred for 40 min to obtain modified nanoparticles;

[0089] The mixed gas is a mixed gas of CO2 and N2, with a volume ratio of 3.5:10;

[0090] S3 silane modification: 100 parts by weight of the modified nanoparticles obtained in step S2 were added to ethanol, 8.5 parts by weight of the composite silane were added, the reaction was stirred at 40 ° C for 2h, centrifuged, washed, and dried to obtain silane-modified nanoparticles;

[0091] The composite silane is phenyl polytrimethylsiloxane and KH580, with a mass ratio of 10:4;

[0092] S4. Preparation of hydrophobic, lipophilic, and skin-friendly ultrafine powder: Add 50 parts by weight of the silane-modified nanoparticles obtained in step S3 to ethanol, add 8.5 parts by weight of macadamia seed oil polyglycerol-6 ester behenate, stir and react for 30 minutes, centrifuge, wash, and dry to obtain a hydrophobic, lipophilic, and skin-friendly ultrafine powder.

[0093] Comparative Example 4

[0094] Compared with Example 3, the difference is that sodium oleate is not added in step S3.

[0095] The details are as follows:

[0096] S3. Surface modification: 10 g of the polydopamine-modified titanium dioxide / zinc oxide nanoparticles prepared in step S2 was added to 100 mL of a 0.12 wt% calcium hydroxide solution, 3.9 g of sodium stearate was added dropwise, the mixed gas was introduced at a flow rate of 4 mL / s, and the reaction was stirred for 40 min to obtain modified nanoparticles;

[0097] The mixed gas is a mixed gas of CO2 and N2 with a volume ratio of 3.5:10.

[0098] Comparative Example 5

[0099] Compared with Example 3, the difference is that sodium stearate is not added in step S3.

[0100] The details are as follows:

[0101] S3. Surface modification: 10 g of the polydopamine-modified titanium dioxide / zinc oxide nanoparticles prepared in step S2 were added to 100 mL of a 0.12 wt% calcium hydroxide solution, 3.9 g of sodium oleate was added dropwise, the mixed gas was introduced at a flow rate of 4 mL / s, and the reaction was stirred for 40 min to obtain modified nanoparticles;

[0102] The mixed gas is a mixed gas of CO2 and N2 with a volume ratio of 3.5:10.

[0103] Comparative Example 6

[0104] Compared with Example 3, the difference is that step S3 is not performed.

[0105] The details are as follows:

[0106] S1. Preparation of titanium dioxide / zinc oxide nanoparticles: 10 g of tetrabutyl titanate and 4 g of zinc acetate were dissolved in 100 mL of ethanol, 0.7 g of polyethylene glycol 400, 5 g of ammonia water and 8 g of water were added, stirred for 40 min, centrifuged, washed, dried, and calcined at 400 ° C for 2 h to obtain titanium dioxide / zinc oxide nanoparticles;

[0107] S2. Polydopamine modification: 10 g of the titanium dioxide / zinc oxide nanoparticles prepared in step S1 was added to 100 mL of water, 3.6 g of dopamine hydrochloride and 0.12 g of the catalyst were added, heated to 45 ° C, stirred for 1.5 h, centrifuged, washed, and dried to obtain polydopamine titanium dioxide / zinc oxide nanoparticles;

[0108] The catalyst is a Tris-HCl solution with a pH of 8.7;

[0109] S3 silane modification: 100 parts by weight of the polydopamine titanium dioxide / zinc oxide nanoparticles prepared in step S2 were added to ethanol, 8.5 parts by weight of the composite silane were added, the reaction was stirred at 40 ° C for 2h, centrifuged, washed, and dried to obtain silane-modified nanoparticles;

[0110] The composite silane is phenyl polytrimethylsiloxane and KH580, with a mass ratio of 10:4;

[0111] S4. Preparation of hydrophobic, lipophilic, and skin-friendly ultrafine powder: Add 50 parts by weight of the silane-modified nanoparticles obtained in step S3 to ethanol, add 8.5 parts by weight of macadamia seed oil polyglycerol-6 ester behenate, stir and react for 30 minutes, centrifuge, wash, and dry to obtain a hydrophobic, lipophilic, and skin-friendly ultrafine powder.

[0112] Comparative Example 7

[0113] Compared with Example 3, the difference is that step S4 is not performed.

[0114] The details are as follows:

[0115] S1. Preparation of titanium dioxide / zinc oxide nanoparticles: 10 g of tetrabutyl titanate and 4 g of zinc acetate were dissolved in 100 mL of ethanol, 0.7 g of polyethylene glycol 400, 5 g of ammonia water and 8 g of water were added, stirred for 40 min, centrifuged, washed, dried, and calcined at 400 ° C for 2 h to obtain titanium dioxide / zinc oxide nanoparticles;

[0116] S2. Polydopamine modification: 10 g of the titanium dioxide / zinc oxide nanoparticles prepared in step S1 was added to 100 mL of water, 3.6 g of dopamine hydrochloride and 0.12 g of the catalyst were added, heated to 45 ° C, stirred for 1.5 h, centrifuged, washed, and dried to obtain polydopamine titanium dioxide / zinc oxide nanoparticles;

[0117] The catalyst is a Tris-HCl solution with a pH of 8.7;

[0118] S3. Surface modification: 10 g of the polydopamine-modified titanium dioxide / zinc oxide nanoparticles prepared in step S2 was added to 100 mL of a 0.12 wt% calcium hydroxide solution, 1.2 g of sodium oleate and 2.7 g of sodium stearate were added dropwise, the mixed gas was introduced at a flow rate of 4 mL / s, and the reaction was stirred for 40 min to obtain modified nanoparticles;

[0119] The mixed gas is a mixed gas of CO2 and N2, with a volume ratio of 3.5:10;

[0120] S4. Preparation of hydrophobic, lipophilic, and skin-friendly ultrafine powder: Add 50 parts by weight of the modified nanoparticles obtained in step S3 to ethanol, add 8.5 parts by weight of macadamia seed oil polyglycerol-6 ester behenate, stir and react for 30 minutes, centrifuge, wash, and dry to obtain a hydrophobic, lipophilic, and skin-friendly ultrafine powder.

[0121] Comparative Example 8

[0122] Compared with Embodiment 3, the difference is that step S5 is not performed.

[0123] The details are as follows:

[0124] S1. Preparation of titanium dioxide / zinc oxide nanoparticles: 10 g of tetrabutyl titanate and 4 g of zinc acetate were dissolved in 100 mL of ethanol, 0.7 g of polyethylene glycol 400, 5 g of ammonia water and 8 g of water were added, stirred for 40 min, centrifuged, washed, dried, and calcined at 400 ° C for 2 h to obtain titanium dioxide / zinc oxide nanoparticles;

[0125] S2. Polydopamine modification: 10 g of the titanium dioxide / zinc oxide nanoparticles prepared in step S1 was added to 100 mL of water, 3.6 g of dopamine hydrochloride and 0.12 g of the catalyst were added, heated to 45 ° C, stirred for 1.5 h, centrifuged, washed, and dried to obtain polydopamine titanium dioxide / zinc oxide nanoparticles;

[0126] The catalyst is a Tris-HCl solution with a pH of 8.7;

[0127] S3. Surface modification: 10 g of the polydopamine-modified titanium dioxide / zinc oxide nanoparticles prepared in step S2 was added to 100 mL of a 0.12 wt% calcium hydroxide solution, 1.2 g of sodium oleate and 2.7 g of sodium stearate were added dropwise, the mixed gas was introduced at a flow rate of 4 mL / s, and the reaction was stirred for 40 min to obtain modified nanoparticles;

[0128] The mixed gas is a mixed gas of CO2 and N2, with a volume ratio of 3.5:10;

[0129] S4. Silane modification: 100 parts by weight of the modified nanoparticles obtained in step S3 were added to ethanol, 8.5 parts by weight of composite silane were added, the reaction was stirred at 40°C for 2h, centrifuged, washed, and dried to obtain silane-modified nanoparticles, which are hydrophobic, lipophilic, and skin-friendly ultrafine powders;

[0130] The composite silane is phenyl polytrimethylsiloxane and KH580, with a mass ratio of 10:4.

[0131] Test Example 1

[0132] The hydrophobic, lipophilic and skin-friendly ultrafine powders prepared in Examples 1-5 of the present invention and Comparative Examples 1-8 were tested for their water and oil (diesel) wetting angles. The results are shown in Table 1.

[0133] Table 1

[0134] Group Water wetting angle (°) Diesel wetting angle (°) Example 1 159 40 Example 2 161 39 Example 3 162 37 Example 4 153 43 Example 5 155 44 Comparative Example 1 152 45 Comparative Example 2 154 42 Comparative Example 3 149 49 Comparative Example 4 132 56 Comparative Example 5 135 62 Comparative Example 6 122 94 Comparative Example 7 129 85 Comparative Example 8

[0135] It can be seen from the above table that the hydrophobic and lipophilic skin-friendly ultrafine powders prepared in Examples 1-3 of the present invention have good hydrophobicity and lipophilicity.

[0136] Example 6

[0137] The present embodiment provides a water-sense long-lasting makeup cushion, comprising: component A1, component A2, component A3, component B and component C, with a mass ratio of 20:18:4:40:0.04.

[0138] Component A1 is prepared from the following raw materials by weight: 8 parts of the hydrophobic, lipophilic and skin-friendly ultrafine powder prepared in Example 1, and 2 parts of caprylic / capric triglyceride;

[0139] Component A2 is prepared from the following raw materials in parts by weight: 10 parts of cyclopentasiloxane and 1 part of trimethylsiloxysilicate;

[0140] Component A3 is prepared from the following raw materials by weight: 0.05 parts of disteardimonium hectorite, 15 parts of polydimethylsiloxane / vinyl polydimethylsiloxane crosspolymer, and 2 parts of PEG-10;

[0141] Component B is prepared from the following raw materials by weight: 35 parts of water, 0.01 parts of disodium EDTA, 0.3 parts of magnesium sulfate, 3 parts of butylene glycol, 2 parts of glycerol, 1 part of 1,2-pentanediol, 0.2 parts of ethylhexylglycerin, and 0.01 parts of phenoxyethanol;

[0142] Component C is fragrance.

[0143] The preparation method comprises the following steps:

[0144] (1) Grind the raw materials of component A1 evenly and set aside;

[0145] (2) Heat component A2 to 80°C, stir and mix evenly, and set aside;

[0146] (3) Add components A1 and A3 to component A2, raise the temperature to 70°C, stir and disperse evenly, and homogenize at 10,000 r / min for 10 minutes;

[0147] (4) Component B was heated to 70° C., added to the system in step (3), homogenized at 10,000 r / min for 15 min, cooled to 40° C., component C was added, stirred evenly, filtered, and filled to obtain a water-based long-lasting makeup cushion.

[0148] Example 7

[0149] The present embodiment provides a water-sense long-lasting makeup cushion, comprising: component A1, component A2, component A3, component B and component C, with a mass ratio of 25:20:5:45:0.07.

[0150] Component A1 is prepared from the following raw materials by weight: 10 parts of the hydrophobic, lipophilic and skin-friendly ultrafine powder prepared in Example 2, and 4 parts of caprylic / capric triglyceride;

[0151] Component A2 is prepared from the following raw materials in parts by weight: 12 parts of cyclopentasiloxane and 1.5 parts of trimethylsiloxysilicate;

[0152] Component A3 is prepared from the following raw materials by weight: 0.1 parts of disteardimonium hectorite, 1.5 parts of polydimethylsiloxane / vinyl polydimethylsiloxane crosspolymer, and 2.5 parts of PEG-10;

[0153] Component B is prepared from the following raw materials by weight: 40 parts of water, 0.02 parts of disodium EDTA, 0.4 parts of magnesium sulfate, 4 parts of butylene glycol, 3 parts of glycerol, 2 parts of 1,2-pentanediol, 0.4 parts of ethylhexylglycerin, and 0.1 parts of phenoxyethanol;

[0154] Component C is fragrance.

[0155] The preparation method comprises the following steps:

[0156] (1) Grind the raw materials of component A1 evenly and set aside;

[0157] (2) Heat component A2 to 85°C, stir and mix evenly, and set aside;

[0158] (3) Add components A1 and A3 to component A2, raise the temperature to 75°C, stir and disperse evenly, and homogenize at 10,000 r / min for 10 minutes;

[0159] (4) Component B was heated to 75° C., added to the system in step (3), homogenized at 10,000 r / min for 15 min, cooled to 45° C., component C was added, stirred evenly, filtered, and filled to obtain a water-based long-lasting makeup cushion.

[0160] Example 8

[0161] The present embodiment provides a water-sense long-lasting makeup cushion, comprising: component A1, component A2, component A3, component B and component C, with a mass ratio of 22:19:4.5:42:0.05.

[0162] Component A1 is prepared from the following raw materials by weight: 9 parts of the hydrophobic, lipophilic and skin-friendly ultrafine powder prepared in Example 3 and 3 parts of caprylic / capric triglyceride;

[0163] Component A2 is prepared from the following raw materials in parts by weight: 11 parts of cyclopentasiloxane and 1.2 parts of trimethylsiloxysilicate;

[0164] Component A3 is prepared from the following raw materials by weight: 0.07 parts of disteardimonium hectorite, 1.2 parts of dimethicone / vinyl dimethicone crosspolymer, and 2.2 parts of PEG-10;

[0165] Component B is prepared from the following raw materials by weight: 37 parts of water, 0.015 parts of disodium EDTA, 0.35 parts of magnesium sulfate, 3.5 parts of butylene glycol, 2.5 parts of glycerol, 1.5 parts of 1,2-pentanediol, 0.3 parts of ethylhexylglycerin, and 0.05 parts of phenoxyethanol;

[0166] Component C is fragrance.

[0167] The preparation method comprises the following steps:

[0168] (1) Grind the raw materials of component A1 evenly and set aside;

[0169] (2) Heat component A2 to 82°C, stir and mix evenly, and set aside;

[0170] (3) Add components A1 and A3 to component A2, raise the temperature to 72°C, stir and disperse evenly, and homogenize at 10,000 r / min for 10 min;

[0171] (4) Component B was heated to 2° C., added to the system in step (3), homogenized at 10,000 r / min for 15 min, cooled to 42° C., component C was added, stirred evenly, filtered, and filled to obtain a water-based long-lasting makeup cushion.

[0172] Example 9

[0173] Compared with Example 3, the difference is that the hydrophobic, lipophilic and skin-friendly ultrafine powder is prepared by Example 4.

[0174] Example 10

[0175] Compared with Example 3, the difference is that the hydrophobic, lipophilic and skin-friendly ultrafine powder is prepared by Example 5.

[0176] Comparative Example 8

[0177] Compared with Example 3, the difference is that the hydrophobic, lipophilic and skin-friendly ultrafine powder is prepared from Comparative Example 1.

[0178] Comparative Example 9

[0179] Compared with Example 3, the difference is that the hydrophobic, lipophilic and skin-friendly ultrafine powder is prepared from Comparative Example 2.

[0180] Comparative Example 10

[0181] Compared with Example 3, the difference is that the hydrophobic, lipophilic and skin-friendly ultrafine powder is prepared from Comparative Example 3.

[0182] Comparative Example 11

[0183] Compared with Example 3, the difference is that the hydrophobic, lipophilic and skin-friendly ultrafine powder is prepared from Comparative Example 4.

[0184] Comparative Example 12

[0185] Compared with Example 3, the difference is that the hydrophobic, lipophilic and skin-friendly ultrafine powder is prepared from Comparative Example 5.

[0186] Comparative Example 13

[0187] Compared with Example 3, the difference is that the hydrophobic, lipophilic and skin-friendly ultrafine powder is prepared from Comparative Example 6.

[0188] Comparative Example 14

[0189] Compared with Example 3, the difference is that the hydrophobic, lipophilic and skin-friendly ultrafine powder is prepared from Comparative Example 7.

[0190] Comparative Example 15

[0191] Compared with Example 3, the difference is that the hydrophobic, lipophilic and skin-friendly ultrafine powder is prepared from Comparative Example 8.

[0192] Comparative Example 16

[0193] Compared with Example 3, the difference is that no hydrophobic, lipophilic and skin-friendly ultrafine powder is added.

[0194] Test Example 2

[0195] The performance of the water-sense long-lasting makeup cushions prepared in Examples 6-10 of the present invention and Comparative Examples 8-16 was tested. The results are shown in Table 2.

[0196] Stability evaluation:

[0197] The prepared products were packed in transparent containers and sealed with lids, and then stored at 50°C for 1 month. The condition of each cosmetic after storage was visually inspected and compared with the product stored at room temperature (control). When no separation, powder aggregation or crystal precipitation was observed compared with the product stored at room temperature, an evaluation of "OK" was given, and when any separation, powder aggregation or crystal precipitation was observed, an evaluation of "NG" was given.

[0198] Sensory evaluation:

[0199] A panel of 20 cosmetic experts (aged 28 to 51) evaluated freshness, nourishment, coverage, and lasting power in the products prepared for a single use on the skin, and the evaluation criteria were as follows.

[0200] A: Very good; B: Excellent; C: Poor; D: Very poor.

[0201] Viscosity:

[0202] The shear viscosity (mPa·s) of the prepared product was measured at 25° C. using a rotational viscometer.

[0203] Table 2

[0204] Group Viscosity (mPa·s) stability Freshness Nourishing Coverage staying power Example 6 15728 OK A A B A Example 7 15889 OK A A A A Example 8 15902 OK A A A A Example 9 15449 OK A B B C Example 10 15602 OK A B B A Comparative Example 8 15321 OK B A B A Comparative Example 9 15194 OK A B B A Comparative Example 10 15002 NG B C C B Comparative Example 11 14982 NG B B B A Comparative Example 12 14995 NG C B B B Comparative Example 13 14772 NG C C C B Comparative Example 14 14451 NG C B B B Comparative Example 15 14882 NG C C C B Comparative Example 16 14229 NG D C C C

[0205] It can be seen from the above table that the water-sense long-lasting makeup cushions prepared in Examples 6 to 8 of the present invention have good stability, freshness, nourishment, coverage and durability.

[0206] Test Example 3

[0207] The water-sense long-lasting makeup cushions prepared in Examples 6 to 10 of the present invention and Comparative Examples 8 to 16 were subjected to sunscreen tests. The results are shown in Table 3.

[0208] The sun protection factor (SPF) was measured using an SPF measuring device "SPF MASTER" (registered trademark) (Shiseido).

[0209] Table 3

[0210] Group SPF value Example 6 32 Example 7 31 Example 8 34 Example 9 28 Example 10 27 Comparative Example 8 22 Comparative Example 9 13 Comparative Example 10 15 Comparative Example 11 23 Comparative Example 12 22 Comparative Example 13 20 Comparative Example 14 18 Comparative Example 15 24 Comparative Example 16 9

[0211] It can be seen from the above table that the water-based long-lasting makeup cushions prepared in Examples 6 to 8 of the present invention have a good sun protection effect.

[0212] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrophobic, lipophilic and skin-friendly ultrafine powder, characterized in that: The specific steps include: S1. Preparation of titanium dioxide / zinc oxide nanoparticles: 9-11 parts by weight of tetrabutyl titanate and 3-5 parts by weight of zinc acetate are dissolved in ethanol, 0.5-1 parts by weight of polyethylene glycol 400, 4-6 parts by weight of ammonia water and 7-10 parts by weight of water are added, the reaction is stirred for 30-50 minutes, centrifuged, washed, dried, and calcined at 350-450° C. for 1-3 hours to obtain titanium dioxide / zinc oxide nanoparticles; S2. Polydopamine modification: 10 parts by weight of the titanium dioxide / zinc oxide nanoparticles prepared in step S1 are added to water, 3-4 parts by weight of dopamine hydrochloride and 0.1-0.2 parts by weight of a catalyst are added, heated to 40-50 ° C, stirred for 1-2h, centrifuged, washed, and dried to obtain polydopamine titanium dioxide / zinc oxide nanoparticles; The catalyst is a Tris-HCl solution with a pH of 8.5-9; S3. Surface modification: 10 parts by weight of the polydopamine-modified titanium dioxide / zinc oxide nanoparticles prepared in step S2 were added to a 0.1-0.15wt% calcium hydroxide solution, 1-2 parts by weight of sodium oleate and 2-3 parts by weight of sodium stearate were added dropwise, and the mixed gas was introduced at a flow rate of 3-5mL / s, and the reaction was stirred for 30-50min to obtain modified nanoparticles; The mixed gas is a mixed gas of CO2 and N2, with a volume ratio of 3-4:10; S4 silane modification: 100 parts by weight of the modified nanoparticles obtained in step S3 were added to ethanol, 7-10 parts by weight of the composite silane was added, the reaction was stirred at 35-45 ° C for 1-3h, centrifuged, washed, and dried to obtain silane-modified nanoparticles; The composite silane is phenyl polytrimethylsiloxane and KH580, with a mass ratio of 10:3-5; S5. Preparation of hydrophobic, lipophilic and skin-friendly ultrafine powder: 50 parts by weight of the silane-modified nanoparticles obtained in step S4 are added to ethanol, 7-10 parts by weight of macadamia seed oil polyglycerol-6 ester behenate are added, the reaction is stirred for 20-40 minutes, centrifuged, washed and dried to obtain a hydrophobic, lipophilic and skin-friendly ultrafine powder.

2. A hydrophobic, lipophilic and skin-friendly ultrafine powder obtained by the preparation method as claimed in claim 1.

3. Use of the hydrophobic, lipophilic and skin-friendly ultrafine powder as claimed in claim 2 in the preparation of cosmetics.

4. A water-based makeup-lasting air cushion, characterized in that: include: The mass ratio of component A1, component A2, component A3, component B and component C is 20-25:18-20:4-5:40-45:0.04-0.07, wherein component A1 is prepared from the following raw materials by weight: 8-10 parts of the hydrophobic, lipophilic and skin-friendly ultrafine powder according to claim 2, 2-4 parts of caprylic / capric triglyceride; component A2 is prepared from the following raw materials by weight: 10-12 parts of cyclopentasiloxane, 1-1.5 parts of trimethylsiloxysilicate; component A3 is prepared from the following raw materials by weight: 0.05-0.1 parts of disteardimonium hectorite, 1-1.5 parts of polydimethylsiloxane / vinyl polydimethylsiloxane crosslinked polymer, PEG-10 2-2.5 parts; component B is prepared from the following raw materials by weight: 35-40 parts of water, 0.01-0.02 parts of disodium EDTA, 0.3-0.4 parts of magnesium sulfate, 3-4 parts of butylene glycol, 2-3 parts of glycerol, 1-2 parts of 1,2-pentanediol, 0.2-0.4 parts of ethylhexylglycerol, and 0.01-0.1 parts of phenoxyethanol; component C is essence.

5. A method for preparing the water-sense long-lasting makeup cushion as claimed in claim 4, characterized in that: The following steps are involved: (1) Grind the raw materials of component A1 evenly and set aside; (2) Heat component A2 to 80-85°C, stir and mix evenly, and set aside; (3) Add components A1 and A3 to component A2, raise the temperature to 70-75°C, and stir to disperse evenly; (4) Raise the temperature of component B to 70-75°C, add it to the system in step (3), homogenize until it is completely emulsified, cool it to 40-45°C, add component C, stir evenly, filter, and fill to obtain a water-based long-lasting makeup cushion.

Citation Information

Patent Citations

  • Graphene plant fiber nano-composite oil absorbent and preparation method thereof

    CN112175580A

  • Finishing process for nano-antibacterial treatment of environment-friendly fabric

    CN113699792A